THE IMPLEMENTATION OF CORE BANKING SYSTEM (CBS) AT PT. BANK SULUT TBK. (PERSERO) - Mait, Priscilla (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2014)
Banking sector has become an integral part of globalization. Banking vital role not only in the conventional activities such as savings and credit, but has become part of the entire electronic transaction activity. The present trend is an online banking application system that owned by almost all existing banking. The purpose of this study is to determine how is the implementation of Core Banking System (CBS) at PT. Bank Sulut. The populations observed in this study are the employees and the customers of PT. Bank Sulut as many as 20 informants. Bank Sulut decided to use the Core Banking Application System OLIBs (Online Integrated Banking System) as the primary system. It has bring a significant change, which are, the increase of validity data and the ease in performing banking functions.The constraint faced by the bank is disturbance in the technology system that caused by the damage condition of hardware and software, power supply, communication networks, and human error. The solution is the company should developing the system into the IT-mandiri system, develop the human resource by training, manage and maintain all the component that related to the system. Keywords: banking, core banking system